Association of prevalent vascular disease with allograft failure and mortality in live‐donor kidney transplant recipients – a retrospective cohort study. (8th July 2019) - Mainra, Rahul; Wong, Germaine; Pilmore, Helen; Lim, Wai H.
Summary: Limited data exist regarding the impact of prevalent vascular disease after live‐donor kidney transplantation. We aimed to determine the associations between the number of prevalent vascular diseases, allograft, and patient outcomes following live‐donor transplantation. This cohort study used data from the Australia and New Zealand Dialysis and Transplant Registry. Rates between recipients of live‐donor kidney transplants ± prevalent vascular disease prior to transplantation were calculated. The associations between vascular disease, allograft failure, and all‐cause mortality were assessed using Cox regression modeling. Kaplan–Meier proportions were used to calculate all‐cause mortality and death with a function graft stratified by vascular disease burden. Of 4742 live‐donor recipients, 428 (9%) and 84 (2%) had prevalent vascular disease at 1 and ≥2 sites, respectively. Compared to recipients without vascular disease, the respective adjusted hazard ratios (95% confidence intervals) for patients with vascular disease at 1 and ≥2 sites were 1.78 (1.41–2.25) and 3.02 (2.03–4.50) for all‐cause mortality; and 1.54 (1.26–1.88) and 2.28 (1.54–3.38) for allograft failure. All‐cause mortality in recipients with vascular disease at 0, 1 and ≥2 sites was 0.028 (0.025, 0.031), 0.090 (0.073, 0.106) and 0.247 (0.196, 0.282) over the first 5‐year post‐transplant. There was an incremental association between the number of prevalent vascular disease sites and risk of allograft failure and all‐cause mortality in live‐donor kidney transplant recipients.